The Use of Quizizz Combine with Flipped Classroom to Improve Vocabulary Mastery SMPN 3 Banjar - Dipayana, I Putu Arya; Dewi, Kadek Sintya; Mahendrayana, Gede (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
This study aimed to improve students’ vocabulary mastery through the implementation of a flipped classroom model assisted by Quizizz. The research employed a Classroom Action Research design conducted in two cycles involving 25 students, with data collected through a pre-test, post-test I, post-test II, and classroom observations. The results showed a gradual improvement in students’ vocabulary mastery, indicated by an increase in the mean score from 71.00 in the pre-test to 73.28 in post-test I and significantly to 85.76 in post-test II. In addition to score improvement, students demonstrated better understanding of word meanings, verb forms, and the use of vocabulary in sentences related to daily activities using the Present Continuous Tense, as well as increased participation and confidence during learning activities. These findings indicate that flipped classroom learning with the aid of Quizizz is an effective instructional strategy for improving students’ vocabulary mastery in English language classrooms.